Finance 4.0 - Towards a Socio-Ecological Finance System A Participatory Framework to Promote Sustainability - Dapp, Marcus M.; Helbing, Dirk; Klauser, Stefan (SpringerBriefs in Applied Sciences and Technology, 2021)
This Open Access book outlines ideas for a novel, scalable and, above all, sustainable financial system. We all know that today's global markets are unsustainable and global governance is not effective enough. Given this situation, could one boost smart human coordination, sustainability and resilience by tweaking society at its core: the monetary system? A Computational Social Science team at ETH Zürich has indeed worked on a concept and little demonstrator for a new financial system, called "Finance 4.0" or just "FIN4", which combines blockchain technology with the Internet of Things ("IoT"). What if communities could reward sustainable actions by issuing their own money ("tokens")? Would people behave differently, when various externalities became visible and were actionable through cryptographic tokens? Could a novel, participatory, multi-dimensional financial system be created? Could it be run by the people for the people and lead to more societal resilience than today's financial system (which is effectively one-dimensional due to its almost frictionless exchange)? How could one manage such a system in an ethical and democratic way? This book presents some early attempts in a nascent field, but provides a fresh view on what cryptoeconomic systems could do for us, for a circular economy, and for scalable, sustainable action.